The value of statistical life : a willingness to accept approach in Singapore road fatality context - Ong, Jia Hon (2015)
This research serves to be the first VOSL study in the context of road fatality in Singapore that employs the WTA elicitation methodology. A significant disparity which exists between WTP and WTA underscores the importance of selecting the right methodology when performing CBA. Research studies have documented WTA to be relatively more appropriate since WTP is often susceptible to problems such as income constraints. However, Singapore lacks existing study which employs WTA methodology in the context of road fatality. Recognising over-bidding and hypothetical biasness as the key constraints of WTA, this paper developed a well-thought survey design that provides policy makers (LTA) with a more representative VOSL figure regarding road safety. Using CVM, valuations were obtained with DBDC valuation methodology. DBDC was chosen due to its high degree of efficiency. 400 face-to-face interviews were conducted with Singaporeans and Permanent Residents and results reflected a mean WTA figure of S$978.03 and a VOSL figure of S$65,202,000. These values are highly robust as they are consistent with results gathered from various countries that employed similar WTA elicitation method. From the regression analysis, income and gender were also found to be significant variables influencing respondents’ WTA valuations, with income having a non-linear relationship. The authors strongly believe that the thoughtful design of survey procedures is one which can be adopted by future WTA studies, beyond the context of road safety. In addition, the said methodology, together with, the VOSL figure found, can be employed by future researchers who are interested in exploring the impacts of inter-temporal changes.